Penerapan Audit Forensik untuk Mengidentifikasi Penipuan Keuangan - Mujahid Syafurddin; Amri Amrulloh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the theoretical foundation of applying forensic audits to identify financial fraud. It focuses on key factors such as auditor competence and professional skepticism, as discussed in various studies. Using a qualitative approach, data were collected through literature review to gather diverse perspectives on forensic audit practices and their effectiveness in detecting financial fraud. By analyzing various journals that employ a quantitative approach, this review identifies key themes such as auditor competency, professional skepticism, and audit techniques used in detecting fraud. The findings indicate that a combination of auditor expertise and skepticism can significantly enhance the effectiveness of forensic audits in detecting financial fraud. This review also concludes that forensic auditing is effective in uncovering various types of fraud.